Nonprofit post-merger identification: Network size, relational heterogeneity, and perceived integration effectiveness - Chen, Bin; Krauskopf, James (Frontiers in Human Dynamics, 2022)
This paper incorporates insights from organizational identity and identification, social network research and post-merger integration to explore factors influencing employees’ identification with a merged nonprofit organization. We propose that nonprofit employees’ identification with the merged nonprofit organization is associated with their network size, relational heterogeneity, and perceived effectiveness of integration processes. Results suggest that employees with larger mentoring and socioemotional support networks exhibit strong post-merger identification. Relational heterogeneity within the workflow network has an inverted U-shape relationship with post-merger identification. Employees’ perceived effectiveness of integration processes significantly influences their identification with new organization. Implications for managing post-merger identification is discussed.